The Ph. D. Jesus Sabourín Fornaris beyond the Universidad de Oriente - Maciel Reyes-Aguilera (Maestro y Sociedad, 2017)
This research focuses on several facets of the educational and promotional work carried out by Dr. Jesús Eduardo Sabourín Fornaris in his life as a librarian, teacher, critic, writer and cultural promoter inside and outside the prestigious Universidad de Oriente, 1950s including the departure to Bulgaria where he resided until his death. It emphasizes the integrality of this intellectual within the Santiago panorama at the end of the neocolonial republic and the vision of some of the personalities who knew him and valued his work. It is an accurate study that shows important data for the history of the first years of the Universidad de Oriente and its teachers, who became intellectuals in a vanguard sociocultural context.